PMCA-Based Detection of Prions in the Olfactory Mucosa of Patients With Sporadic Creutzfeldt–Jakob Disease - Cazzaniga, Federico Angelo; Bistaffa, Edoardo; De Luca, Chiara Maria Giulia; Portaleone, Sara Maria; Catania, Marcella; Redaelli, Veronica; Tramacere, Irene; Bufano, Giuseppe; Rossi, Martina; Caroppo, Paola; Giovagnoli, Anna Rita; Tiraboschi, Pietro; et al. (Frontiers in Aging Neuroscience, 2022)
Sporadic Creutzfeldt-Jakob disease (sCJD) is a rare neurodegenerative disorder caused by the conformational conversion of the prion protein (PrPC) into an abnormally folded form, named prion (or PrPSc). The combination of the polymorphism at codon 129 of the PrP gene (coding either methionine or valine) with the biochemical feature of the proteinase-K resistant PrP (generating either PrPSc type 1 or 2) gives rise to different PrPSc strains, which cause variable phenotypes of sCJD. The definitive diagnosis of sCJD and its classification can be achieved only post-mortem after PrPSc identification and characterization in the brain. By exploiting the Real-Time Quaking-Induced Conversion (RT-QuIC) assay, traces of PrPSc were found in the olfactory mucosa (OM) of sCJD patients, thus demonstrating that PrPSc is not confined to the brain. Here, we have optimized another technique, named protein misfolding cyclic amplification (PMCA) for detecting PrPSc in OM samples of sCJD patients. OM samples were collected from 27 sCJD and 2 genetic CJD patients (E200K). Samples from 34 patients with other neurodegenerative disorders were included as controls. Brains were collected from 26 sCJD patients and 16 of them underwent OM collection. Brain and OM samples were subjected to PMCA using the brains of transgenic mice expressing human PrPC with methionine at codon 129 as reaction substrates. The amplified products were analyzed by Western blot after proteinase K digestion. Quantitative PMCA was performed to estimate PrPSc concentration in OM. PMCA enabled the detection of prions in OM samples with 79.3% sensitivity and 100% specificity. Except for a few cases, a predominant type 1 PrPSc was generated, regardless of the tissues analyzed. Notably, all amplified PrPSc were less resistant to PK compared to the original strain. In conclusion, although the optimized PMCA did not consent to recognize sCJD subtypes from the analysis of OM collected from living patients, it enabled us to estimate for the first time the amount of prions accumulating in this biological tissue. Further assay optimizations are needed to faithfully amplify peripheral prions whose recognition could lead to a better diagnosis and selection of patients for future clinical trials.